Drug Delivery Using Nanoparticles for Cancer Stem-Like Cell Targeting - Lu, Bing; Huang, Xiaojia; Mo, Jingxin; Zhao, Wei (Frontiers in Pharmacology, 2016)
The theory of cancer stem-like cell (or cancer stem cell, CSC) has been established to explain how tumor heterogeneity arises and contributes to tumor progression in diverse cancer types. CSCs are believed to drive tumor growth and elicit resistance to conventional therapeutics. Therefore, CSCs are becoming novel target in both medical researches and clinical studies. Emerging evidences showed that nanoparticles effectively inhibit many types of CSCs by targeting various specific markers (aldehyde dehydrogenases, CD44, CD90, and CD133) and signaling pathways (Notch, Hedgehog, and TGF-β), which are critically involved in CSC function and maintenance. In this review, we briefly summarize the current status of CSC research and review a number of state-of-the-art nanomedicine approaches targeting CSC. In addition, we discuss emerging therapeutic strategies using epigenetic drugs to eliminate CSCs and inhibit cancer cell reprogramming.